Strategi Bimbingan Guru Mengungkap Kemampuan Literasi dan Karakter Siswa Menyongsong Abad 21 - Huzaemah, Siti (Tarbawi, 2019)
This paper aims to describe the strategy to determine the literacy abilities and character students on the subject of reproduction in organisms, an as effort to equip life skill to approaching the 21st century. The research used a qulitative method with research subjects were student of class IX G SMPN 1 Baros in the 2018/2019 academic year. The research instrument used was in the form of a rubric which scoring the report and the scoring sheet between individuals on the following characters: one that can work together, be responsible, and care for the environment. The results showed there were 16 students or 52 % demonstrated literacy skills accordinng to the teacher’s requirements, while 15 students or 48 % were showed inadequate. Considering the observed characters, students already have good responsible character category with a total score 85, and also showed a character that capable of cooperating with good category with a total score of 89. However, for characteristic the showed environmental caring was only obtained a score of 46, the lowest among all categories. Therefore, it can be concluded that the teacher’s guidance startegy that included the stages of writing, grades, revisions, typing, sending and editing were able to reveal the literacy abilities and character of students more objectively on the subject of reproduction in organisms, as an effort to equip life skills to approaching the 21st century.